2003
DOI: 10.1002/anie.200390237
|View full text |Cite
|
Sign up to set email alerts
|

Sc3N@C68: Folded Pentalene Coordination in an Endohedral Fullerene that Does Not Obey the Isolated Pentagon Rule

Abstract: organization of 1 into a liquid-crystalline phase is that it allows the unprecedented control of the molecular orientation of 1 in thin solid films. Induced orientation of the liquidcrystalline domains of 1 under a shearing force results in highly anisotropically ordered thin solid films that serve as dichroic polarizers of light at long wavelengths (greater than 600 nm). Future work will investigate the fluorescence, semiconducting, and photoconducting properties of 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
76
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(87 citation statements)
references
References 15 publications
7
76
0
4
Order By: Relevance
“…7 Almost any free-base porphyrin or metalloporphyrin (or like macrocycle) can be cocrystallized with almost any fullerene (or derivatized fullerene) from comixed solutions. [8][9][10][11][12][13] Representative examples are illustrated by H 2 TPP‚ C 60 ‚3toluene (H 2 TPP ) tetraphenylporphyrin) and 2Co-(OEP)‚C 60 ‚CHCl 3 (OEP ) dianion of octaethylporphyrin). As shown in Figures 2 and 3, the structures often adopt an alternating zigzag motif.…”
Section: Fullerene-porphyrin and Fullerene-metalloporphyrin Cocrystalmentioning
confidence: 99%
“…7 Almost any free-base porphyrin or metalloporphyrin (or like macrocycle) can be cocrystallized with almost any fullerene (or derivatized fullerene) from comixed solutions. [8][9][10][11][12][13] Representative examples are illustrated by H 2 TPP‚ C 60 ‚3toluene (H 2 TPP ) tetraphenylporphyrin) and 2Co-(OEP)‚C 60 ‚CHCl 3 (OEP ) dianion of octaethylporphyrin). As shown in Figures 2 and 3, the structures often adopt an alternating zigzag motif.…”
Section: Fullerene-porphyrin and Fullerene-metalloporphyrin Cocrystalmentioning
confidence: 99%
“…[8][9][10][11][12][13] Representative examples are illustrated by H 2 TPP‚ C 60 ‚3toluene (H 2 TPP ) tetraphenylporphyrin) and 2Co-(OEP)‚C 60 ‚CHCl 3 (OEP ) dianion of octaethylporphyrin). As shown in Figures 2 and 3, the structures often adopt an alternating zigzag motif.…”
Section: Fullerene-porphyrin and Fullerene-metalloporphyrin Cocrystalmentioning
confidence: 99%
“…B 55 , B 56 and B 66 imply that the corresponding metallic atoms are located toward a 5:5, 5:6 and 6:6 bond, respectively; R 6 implies that the corresponding metallic atoms are located toward a hexagon. Theoretical investigations demonstrated that charged C 68 -6140 is the most stable isomer among the eleven candidates satisfying 13 C NMR experimental results of Sc 3 N@C 68 [20,34] . Theoretical and experimental results demonstrated that the three Sc atoms in Sc 3 N@C 68 are all located toward the fused junction of two pentagons [14,20,21,23,31] .…”
Section: N@c 68mentioning
confidence: 88%